EU Environmental and Climate Policies as a Source of Development Challenges for the Enterprise Sector - Jakub GRABOWSKI (Communications of International Proceedings, 2021)
The development of enterprises is affected by a number of factors, many of which are economic or legal, which entrepreneurs have to adapt to, having no other option at hand. This group undoubtedly includes environmental and climate challenges. In the coming years, Polish and the European economies will face a number of challenges resulting from environmental and climate policies at both the EU and national levels. According to, for example, the European Green Deal document, the EU is to become climate neutral by 2050. The implementation of solutions in the field of circular economy is one of the elements for reaching climate neutrality. These challenges relate to a number of areas related to energy efficiency leading to the reduction of greenhouse gas emissions, but also to the broadly understood resource management. In the result, the requirement to develop sustainable products, services and business models will become the norm and it will transform consumption patterns so that waste will be prevented in the first place. It concerns such issues as: improving the durability and service life of products, their reusability, increasing energy efficiency and resource efficiency, enabling product regeneration and high-quality recycling, reducing disposable items and preventing premature aging of products, or the use of the "product-as-a-service" model and other models in which manufacturers remain responsible for products throughout their life cycle. Striving to trigger changes in the aforedescribed ranges described important not only from a business point of view, but also in terms of corporate social responsibility. In the first context, it should be emphasized that the implementation of changes in companies in line with the described trend does not preclude the achievement of the assumed development goals. Additionally, it can have a long-term impact on environmental and climate issues.
Keywords: Environmental and Climate Challenges; Strategic Enterprise Development; Circular Economy.